A Reductive Deuteration Approach to the Efficient Synthesis of Deuterated Polymers - Ning, Lei; Wang, Lijun; Peng, Mengqi; Qin, Zixuan; Li, Hengzhao; Liu, Shangzhong; Dong, Yanhong; An, Jie (Synlett, 2022)
Deuterated polymers have wide applications but limited synthetic methods. In this study, we report an efficient two-step approach for the synthesis of deuterated polyesters and polyurethanes. Firstly, two practical single-electron transfer (SET) reductive-deuteration methods have been developed for site-selective introduction of C(sp3)–D into diol monomers. Nine deuterated diol monomers with high deuterium incorporations were synthesized under SmI2–D2O and/or Na-EtOD-d1 SET reductive-deuteration conditions. Then, six typical deuterated polyesters and polyurethanes were synthesized using those deuterated monomers under typical polymerization conditions. In all the synthesized polymers, high deuterium incorporation was fully maintained, which showcased the potential application of this approach for the synthesis of polymers with site-specific deuterium labelling.
Keywords: reductive deuteration; single electron transfer; deuterated diol; deuterated polymer; selective deuteration